2021
DOI: 10.3390/jcm10143194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Psoriatic Arthritis and Rheumatoid Arthritis Patients across Body Mass Index Categories in Switzerland

Abstract: Abnormal body mass index (BMI) was associated with worse rheumatic markers in psoriatic arthritis (PsA) and rheumatoid arthritis (RA). Aiming to describe PsA and RA patients stratified by BMI, we performed a descriptive study in PsA and RA patients (two distinct cohorts) in the Swiss Clinical Quality Management in Rheumatic Diseases (SCQM) registry. New users of biologic or targeted synthetic disease-modifying anti-rheumatic drugs (b/tsDMARDs) were stratified by BMI at the start of their treatment (underweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
(76 reference statements)
2
11
0
Order By: Relevance
“…Finally, as described elsewhere, 12 the prevalence of overweight and obesity were higher among patients with PsA in comparison to the general population in Switzerland (Switzerland 2017, people >15 years old, 31% overweight and 11% obese). 36 Higher obesity prevalence among patients with PsA in comparison to the reference population was in agreement with prior studies.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Finally, as described elsewhere, 12 the prevalence of overweight and obesity were higher among patients with PsA in comparison to the general population in Switzerland (Switzerland 2017, people >15 years old, 31% overweight and 11% obese). 36 Higher obesity prevalence among patients with PsA in comparison to the reference population was in agreement with prior studies.…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, we classified patients with BMI <25 kg/m 2 as normal weight, including patients with BMI <18.5 kg/m 2 , who may be classified as underweight. This was done due to low prevalence of underweight patients with PsA in SCQM 12 and is consistent with previous practice in PsA 10 26 and other inflammatory rheumatic diseases research in which the majority of studies combine normal and underweight patients. 41 It was suggested that patients with obesity may benefit from other non-TNFi b/tsDMARDs, however, the evidence is limited.…”
Section: Strengths and Limitationssupporting
confidence: 55%
See 2 more Smart Citations
“…Rheumatoid arthritis (RA), with a prevalence of 0.5 to 1.0% [ 1 ], affects women three times more frequently than men [ 2 , 3 ]. While the reason for this unbalanced frequency between women and men is not fully understood, it is known as the result from multiple factors, including both biologically-driven sex concepts and socially constructed gender factors.…”
Section: Introductionmentioning
confidence: 99%